2021
DOI: 10.1002/admi.202100505
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Degradation of CH3NH3PbI3 Propagate from PEDOT:PSS Interface in the Presence of Humidity

Abstract: Understanding interfacial reactions that occur between the active layer and charge‐transport layers can extend the stability of perovskite solar cells. In this study, the exposure of methylammonium lead iodide (CH3NH3PbI3) thin films prepared on poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)‐coated glass to 70% relative humidity (R.H.) leads to a perovskite crystal structure change from tetragonal to cubic within 2 days. Interface‐sensitive photoluminescence measurements indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has been reported that PSS on the surface of the PEDOT:PSS layer can react with organic ammonium salt molecules in perovskites, resulting in the formation of defective perovskite grains. 19 Thus, the presence of CEPA molecules on the PEDOT:PSS surface leads to a reduction of non-uniform nucleation sites and thus improves the quality of perovskite crystals at the buried interface. Furthermore, the perovskite films were also prepared at a normal concentration of 1.0 M. The perovskite film prepared on the control PEDOT:PSS displayed a small amount of white precipitate, which is commonly attributed to impurity phases due to inhomogeneous crystallisation, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PSS on the surface of the PEDOT:PSS layer can react with organic ammonium salt molecules in perovskites, resulting in the formation of defective perovskite grains. 19 Thus, the presence of CEPA molecules on the PEDOT:PSS surface leads to a reduction of non-uniform nucleation sites and thus improves the quality of perovskite crystals at the buried interface. Furthermore, the perovskite films were also prepared at a normal concentration of 1.0 M. The perovskite film prepared on the control PEDOT:PSS displayed a small amount of white precipitate, which is commonly attributed to impurity phases due to inhomogeneous crystallisation, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…18 However, the acidic and hygroscopic nature of PEDOT:PSS would lead to interfacial interactions with Sn perovskite, which is highly detrimental to the device performance of Sn-PSCs. 19,20 It has been found that high defect density at the Sn perovskite/ PEDOT:PSS interface could lead to severe non-radiative recombination and poor charge carrier extraction/transport in Sn-PSCs, resulting in signicant losses in open circuit voltage (V OC ) and short-circuit current density (J SC ). [21][22][23] Besides, PSS is usually enriched on the surface of PEDOT:PSS, making it electrically insulating and hygroscopic at the buried interface of PEDOT:PSS-based Sn-PSCs, which causes further deterioration of carrier collection efficiency and induces a buried interface-related degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The surface wettability and topography of the HTL and its interfacial interactions, which affect the nucleation and crystallization quality of the perovskite lm and its solar cell performance, are also critical to consider. 12,32,38 In this regard, we have studied the surface wettability effect of PEDOT:PSS (PH, PH1000, and AI4083) and three mixtures of (PH:PH1000 and PH:AI4083) in a 1 : 1 ratio, and (PH:PH1000:AI4083) in 1 : 1 : 1 ratio on the nucleation and crystallization of overcast perovskite lms and corresponding solar cell performances. Table 1 displays the factory properties of three commercially available PEDOT:PSS, selected in this study and most commonly utilized as HTL in inverted PSCs.…”
Section: Work Functions and Surface Properties Of Pedot:pss Lmsmentioning
confidence: 99%
“… 31 Thomas et al investigated the chemical and structural degradation of MAPbI 3 propagated from PEDOT:PSS AI4083 surface at 70% relative humidity and discovered that the perovskite/PEDOT:PSS interface is a critical driving factor for such instability. 32 Because faulty regions cause deterioration to spread across the active area, 25 perovskite film preparation and crystallization are essential in producing smooth grains of considerable size. As a result, the perovskite layer's film quality and properties are critical in determining device performance and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Also, doping (CH 3 NH 2 CH 3 ) + with Cs + in the A site causes octahedra tilt, which induces bandgap increment and improves the resulting perovskite solar cell stability (Eperon et al, 2020). To improve stability and preserve power conversion efficiency, (CH 3 ) 2 NH + 2 is partially substituted in the A site of CH 3 NH 3 PbI 3 , changing the tetragonal crystal structure to a cubic structure when exposed to humidity, further exposure to humidity resulting in phase change into a hexagonal structure (Thomas et al, 2021). The spectroscopic limited maximum efficiency (SLME) is aimed at screening materials based on their intrinsic properties such as the bandgap, the absorption spectra, and the non-radiative combination loss (Yu and Zunger, 2012).…”
Section: Introductionmentioning
confidence: 99%